PERAMALAN PRODUKSI JAGUNG PROVINSI NUSA TENGGARA TIMUR DENGAN METODE SEASONAL AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (SARIMA) - Leonar Do Da'Vinci T.; Cindy Artha Yunita Hutabarat (Badan Pusat Statistik Provinsi NTT, 2025)
Nusa Tenggara Timur Province is one of the centers of maize production in Indonesia, so this commodity requires special attention. The Nusa Tenggara Timur Provincial Government has designated the agricultural sector as part of the pillars of the sustainable economy with the hope that maize production will be sustainable and can be optimized in the future through agricultural modernization. Supporting this sustainability certainly requires good planning, one of which is forecasting potential maize production as a basis for policy interventions to optimize maize production in the future. Therefore, this study focuses on generating maize production forecasting data. This study uses the Seasonal Autoregressive Integrated Moving Average (SARIMA) method to develop an appropriate forecasting model. This is based on maize production patterns in Nusa Tenggara Timur Province, which exhibit seasonal patterns. Based on the results of identifying the best SARIMA model, the selected forecasting model is SARIMA (0,0,0)(1,1,0)12. After forecasting for the next twelve months, the highest maize production will be achieved in April 2026 with an estimated maize production of 201,772.94 tons, while the lowest corn production will occur in November 2025 with maize production of 6,675.90 tons. Based on these findings, the government is expected to optimize the planting period because the maize production pattern in East Nusa Tenggara Province, based on the forecast results, still depends on certain periods, especially the rainy season. Optimizations that can be carried out include: expanding the planting area, using superior seeds, pesticides, fertilizers, accompanied by expanding access to the users and increasing the planting index. The planting index can be increased with proper water management, especially in the dry season, for example by implementing drip irrigation so that maize planting does not only depend on the season.